Brand Equity as a Moderator in the Relationship between Social Media Marketing, e-WOM, and Purchase Intention: Implications for Educational Marketing Management - Doris Walfauzi; vidyarini Dwita (Journal of Educational Management Research, 2026)
This study aims to examine the influence of social media marketing and electronic word of mouth (e-WOM) on purchase intention, with brand equity as a moderating variable, from an educational marketing management perspective. A quantitative approach was employed using purposive sampling. The sample consisted of 150 respondents who are users of digital commerce platforms and are familiar with the studied brand. Data were collected through online questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that social media marketing and e-WOM have positive and significant effects on purchase intention. Furthermore, brand equity significantly moderates the relationship between both independent variables and purchase intention, strengthening their effects. These findings suggest that the effectiveness of digital marketing strategies is enhanced when supported by strong brand equity and positive consumer perceptions. From an educational marketing management perspective, this study highlights the importance of integrating digital literacy and strategic marketing education in building sustainable brand value. Organizations should develop structured learning strategies to enhance consumer engagement and brand perception in digital environments.